2017
DOI: 10.4314/sajas.v47i6.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary <i>Aloe vera</i> crude extracts on digestive enzyme activities and muscle proximate composition of GIFT tilapia juveniles

Abstract: This study investigated the effects of dietary Aloe vera powder extract on the activities of digestive enzymes and muscle composition of Oreochromis niloticus (GIFT strain) juveniles. Five dietary groups were formulated in which A. vera powder was added into a tilapia feed at 0.5%, 1.0%, 2.0%, and 4%/kg feed, and fed for eight weeks. Amylase, trypsin, and lipase activities in the liver and along the alimentary canal (stomach, midgut, and hindgut) varied significantly between dietary groups. Amylase activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, in this study, no significant difference in growth was found between fish with dietary AMP levels of 4000 mg/kg and 8000 mg/kg. These results are consistent with those on Aloe vera polysaccharide supplementation in African catfish [38], which might be due to higher feed additive levels affecting intestinal morphology, feed digestibility, and absorption [39,40].…”
Section: Discussionsupporting
confidence: 90%
“…However, in this study, no significant difference in growth was found between fish with dietary AMP levels of 4000 mg/kg and 8000 mg/kg. These results are consistent with those on Aloe vera polysaccharide supplementation in African catfish [38], which might be due to higher feed additive levels affecting intestinal morphology, feed digestibility, and absorption [39,40].…”
Section: Discussionsupporting
confidence: 90%
“…This as a result improves feed digestibility and availability of nutrients from feedstuffs, and shortens the feed transit time, which might have beneficial influence on digestive enzymes (Platel and Srinivasan 2004) as well as minimizing the amount of feed substrate available for proliferation of pathogenic bacteria (Citarasu 2010). Feed digestibility enhancement in fish following herbal extract administration was supported by our previous study (Gabriel et al 2017), which reported that 100% A. vera extracts had significantly increased amylase, trypsin, and lipase activities in GIFT. The same herb was also reported to have improved gastrointestinal morphology of O. mykiss by increasing intestinal villi lengths and intestinal surface area for increased feed digestion and absorption capacity of the gut (Heidarieh et al 2013).…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, when the rosemary was added to the feed of sea bass with an average weight of 20.43 g, no significant change was observed in the whole-body proximate composition (p>0.05) (Yılmaz et al, 2012). Gabriel et al (2017) found in their study that aloe vera plant did not change the amount of moisture, ash, or lipid in tilapia juveniles, but it reduced the amount of protein. In light of all these studies, it is seen that plant sources, with the components they contain, make positive or negative changes in fish meat nutritional values.…”
Section: Resultsmentioning
confidence: 87%